Characterization of smallholder pig production systems in Uganda: constraints and opportunities for engaging with market systems - Ouma, Emily; Dione, Michel; Lule, Peter; Rosel, Kristina; Pezo, Danilo (African Association of Agricultural Economics, 2013)
Pig production has increasingly become an important activity, especially among smallholder farmers in Uganda in the past three decades as evidenced by a dramatic rise in pig population from 0.19 to 3.2 million. This is linked to the rise in demand for pork due to preference changes among other factors. Per capita consumption of pork has been estimated at 3.4 kg/person/year representing a ten-fold increase in the last 30 years. Pigs are important assets for the poor smallholders in Uganda generating income for meeting planned and emergency household financial needs. Despite its importance, the smallholder pig systems are faced with a number of productivity and market related constraints ranging from diseases, poor nutrition and poorly organized markets. Strong growth opportunities to improve smallholder pig systems exist if the constraints are minimized. However the constraints and opportunities vary among smallholder producers as they are not a homogenous group and are affected by various factors. This paper applies a cluster analysis to characterize smallholder pig production systems into typologies in three districts in Uganda by utilizing village level data from 35 villages. The paper further explores the constraints and opportunities for the different typologies to engage with output and input market systems. The paper concludes that different interventions are necessary to improve market linkages with the smallholder pig production systems due to their varying differences in terms of farmers’ cooperative involvement, institutional linkages and intensification related indicators.
Keywords: Smallholder pig production systems; Market systems; Typologies; Cluster analysis; Uganda